Clay mineralogy and thermal history of the Neogene Vinchina Basin, central Andes of Argentina: Analysis of factors controlling the heating conditions - Collo, Gilda (2011)
The Vinchina Foreland Basin, western Argentina, contains a ∼7 km thick nonmarine stratigraphy, chronologically constrained within the Mio-Pliocene (circa 19-3.4 Ma), and where distribution of Illite/Smectite interstratified phases has shown a progressive smectite-illitization progress (R0 → R1 → R3), is consistent with an incipient burial history. R0 represents randomly mixed-layered illite/smectite normally found at shallow depths, as this ordering is not stable at ∼120C. In the Vinchina Basin, however, the R0 is still persistent at ∼7 km depth, and its appearance even in the deepest levels is consistent with previous interpretations of low burial temperatures based on thermochronologic studies of detrital apatites. The maximum paleotemperature estimation and basin depth imply geothermal gradient as low as ∼15C/km, which allowed an estimate of heat flow values between 33 and 42 mW/m2, that would rise to between ∼40 and 51 mW/m2 when the sedimentation rate (thermal blanketing) is taken into account. These values were only reported for cold basins and represent a paleothermal state of a refrigerated lithosphere. We suggest the central Andes were dominated since the Miocene by heat transfer derived mostly from crustal contributions with a minimum input from the asthenosphere. This refrigerated lithosphere is typical of segments affected by flat subduction. Preliminary thermal models based on previous geodynamic approaches support our conclusions.